Mobile Flowering Locus T RNA – Biological Relevance and Biotechnological Potential - Yu, Zhiming; Chen, Weiwei; Wang, Yue; Zhang, Pengcheng; Shi, Nongnong; Hong, Yiguo (Frontiers in Plant Science, 2022)
Many systemically mobile mRNAs have been revealed in phloem. However, very few of them have been found to be of clear signaling functions. One of such rare examples is the mobile Flowering locus T (FT) mRNA despite the continuous debate about its mobility and biological relevance to the control of flowering time in plants. Nevertheless, accumulating evidence supports the notion of the long-distance movement of FT mRNA from leaf to shoot apex meristem and its role in flowering. In this review, we discuss the discovery of florigenic FT, the initial debate on long-distance movement of FT mRNA, emerging evidence to prove its mobility, and the use of mobile FT mRNA to generate heritable transgenerational gene editing in plants. We elaborate on evidence from virus-based RNA mobility assay, plant grafting, RNA with fluorescent protein labeling, and CRISPR/Cas9 gene-editing technology, to demonstrate that the FT mRNA besides the FT protein can move systemically and function as an integral component of the florigenic signal in flowering. We also propose a model to prompt further research on the molecular mechanism underlying the long-distance movement of this important mobile signaling RNA in plants.